2013
DOI: 10.2105/ajph.2013.301492
|View full text |Cite
|
Sign up to set email alerts
|

Food Sources of Saturated Fat and the Association With Mortality: A Meta-Analysis

Abstract: We summarized the data related to foods high in saturated fat and risk of mortality. We searched Cochrane Library, MEDLINE, EMBASE, and ProQuest for studies from January 1952 to May 2012. We identified 26 publications with individual dietary data and all-cause, total cancer, or cardiovascular mortality as endpoints. Pooled relative risk estimates demonstrated that high intakes of milk, cheese, yogurt, and butter were not associated with a significantly increased risk of mortality compared with low intakes. Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
114
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(123 citation statements)
references
References 50 publications
3
114
0
6
Order By: Relevance
“…There is a need for rendering food-based guidelines more practical, scientifically sound, and easily understandable. When we considered isocaloric replacement of MUFA by SFA we observed a higher mortality risk, in accordance with results from previous studies [26,30], denoting the importance of not considering all fats as detrimental.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There is a need for rendering food-based guidelines more practical, scientifically sound, and easily understandable. When we considered isocaloric replacement of MUFA by SFA we observed a higher mortality risk, in accordance with results from previous studies [26,30], denoting the importance of not considering all fats as detrimental.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, it is essential to consider the context in which meat consumption is evaluated. For example, the effects seem to differ in Asian populations [20,22,26]; in low-income countries small amounts of added meat may significantly improve micronutrient deficits [3]. The novelty of our results relies on three points: 1) We compared in the same cohort the rates of all-cause mortality associated with red/processed meat and with SFA.…”
Section: Discussionmentioning
confidence: 99%
“…all-cause mortality risk (30,31), more recently Michaëlsson et al (20) reported a higher risk of CVD, cancer, and allcause mortality with high milk consumption in Sweden. The roles of other dairy foods, such as yogurt or cheese, in mortality risk are less clear (20,21,(23)(24)(25).…”
mentioning
confidence: 99%
“…In view of the fact that diet and lifestyles of vegetarians may differ from those of non-vegetarians, it is likely that the benefits are not to be ascribed to the absence of meat intake only. In another meta-analysis by O'Sullivan et al (13) , some studies included white meat in the category of total meat. Besides, another study by Larsson and Orsini (14) did not analyse the cause-specific mortality.…”
mentioning
confidence: 99%